2013
DOI: 10.1371/journal.pone.0077761
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant Infusion of Donor B Cells Enhances Donor-Specific Skin Allograft Survival

Abstract: Pretransplant donor lymphocyte infusion (DLI) has been shown to enhance donor-specific allograft survival in rodents, primates and humans. However, the cell subset that is critical for the DLI effect and the mechanisms involved remain elusive. In this study, we monitored donor cell subsets after DLI in a murine MHC class I Ld-mismatched skin transplantation model. We found that donor B cells, but not DCs, are the major surviving donor APCs in recipients following DLI. Infusing donor B, but not non-B, cells res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The establishment of donor antigen‐specific tolerance has been shown to enhance skin allograft survival, such as pre‐transplant donor B lymphocytes, induced immature dendritic cells, and bioengineering thymus organoids to restore thymus function . Previous studies have showed that ECDI‐SP treatment holds great potential in inducing graft tolerance and prolonging graft survival, including islet, heart, and kidney in mice or rats .…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of donor antigen‐specific tolerance has been shown to enhance skin allograft survival, such as pre‐transplant donor B lymphocytes, induced immature dendritic cells, and bioengineering thymus organoids to restore thymus function . Previous studies have showed that ECDI‐SP treatment holds great potential in inducing graft tolerance and prolonging graft survival, including islet, heart, and kidney in mice or rats .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated the subsets of allogeneic donor cells that may be important for inhibiting anti-donor immune responses, but the results remain controversial [ 37 42 ]. A previous study demonstrated that a single injection of naïve donor SPL B cells prior to transplantation resulted in significantly prolonged donor-specific skin allograft survival compared to that of the infusion of non-B cells in an MHC class I-mismatched model [ 43 ], indicating the important role of donor B cells in prolonging the survival of donor-specific skin allografts. However, a significant immune-regulatory effects of injection with SPL B cells has not been demonstrated in a MHC class I/II-mismatched model using a fully allogeneic combination.…”
Section: Discussionmentioning
confidence: 99%